Early second trimester hCG of maternal serum as predictor marker for pregnancy induced hypertension - Munirah Md Mansor; Khalidah MB; Dian Nasriana N; Hanita O; Nor Azlin MI (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Pregnancy induced hypertension (PIH) is commonly encountered in hypertensive disease in pregnancy (HDP) and important cause of feto-maternal morbidity and mortality. Abnormal changes of placenta development in PIH leads to abnormal elevation of second trimester maternal hCG level. Thus, it may have a role in prediction of PIH. The objective of this study was to evaluate the ability of serum hCG levels during early second trimester to predict PIH and obstetric outcome at later gestation. We conducted a cohort study which comprised 34 pregnant women varying from 14–20 weeks of gestation with serum hCG level taken at points of recruitment. Serum hCG was measured by a chemiluminescent immunoassay. Three (8.8%) pregnant women developed late onset PIH while the remainder were normotensive. The diagnostic performance of second trimester hCG in predicting PIH as assessed by receiver operator characteristic curve was poor (AUC = 0.398). Multiple of median (MoM) were used to improve the hCG performance and MoM of >2 MoM were considered as elevated hCG level. All pregnancies with PIH had <2 MoM. In normotensive pregnancy, 29 (93.5%) women had hCG <2 MoM and 2 (6.5%) women had hCG >2 MoM (p>0.655). There was no significant association of hCG level and pregnancy outcome. In conclusion, estimation of second trimester hCG is a poor predictive marker for PIH. These findings are limited by the less number of hypertensive cases.